A review on the effects of saffron extract and its constituents on factors related to neurologic, cardiovascular and gastrointestinal diseases - AR Milajerdi; V Bitarafan; M Mahmoudi (Institue of Medicinal Plants, ACECR, 2015)
Background: Saffron (Crocus satious L.) provides a variety of promising preventive and therapeutic effects with non-considerable side effects. Objective: Based on our knowledge, this is the first study that simultaneously has reviewed the effect of saffron extract and its constituents on the factors associated with neuropsychological, cardiovascular, and gastrointestinal tract diseases. Methods: To search studies, an open-ended, language-restricted (English) search of MEDLINE (PubMed) and Science direct databases were conducted (up to 28 October 2014) using specific search criteria to identify all related studies. In addition the SID and Magiran databases were also searched for Persian articles. Results: Results show that the saffron and its constituents can be beneficial for prevention and treatment of diseases related to memory and eye. However, studies about analgesic, anti-inflammatory and anti-seizure effects of saffron are few, the results are promising. The effects of saffron and its constituents on anxiety and insomnia have been only studied in animal models and the results are promising. Their antidepressants effects are also very evident. On the other hand, the effects of saffron and its active constituents in prevention and treatment of cardiovascular diseases have also been observed in previous studies. Although the studies about saffron effects on gastrointestinal diseases are few and only in animal models, they have shown potential benefits in prevention and treatment. Conclusion: It seems that saffron and its constituents have preventive and therapeutic roles in neurologic, cardiovascular and gastrointestinal diseases. These functions are contributed to antioxidant, anti-inflammatory and anti-apoptotic properties of saffron.